2009
DOI: 10.1111/j.1469-0691.2008.02670.x
|View full text |Cite
|
Sign up to set email alerts
|

Transmission permeability of tuberculosis involving immigrants, revealed by a multicentre analysis of clusters

Abstract: In recent years, the number of cases of tuberculosis (TB) among immigrants in Spain has increased markedly, and led to this analysis of the recent transmission patterns of TB in the immigrant population in Madrid. The countries from which the highest number of immigrant cases have been reported were Ecuador (21%), Romania (16%), Morocco (12%), Peru (11%) and Bolivia (9%). Fifty-one per cent of the cases were from South America. In a multicentre study (2004-2006), IS6110 restriction fragment length polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Nineteen percent of the immigrant clusters (involving 42.5% of the MTB isolates) were found to be large and most of these were multinational and/or mixed, consistent with the high transmission permeability identified in Madrid [15].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Nineteen percent of the immigrant clusters (involving 42.5% of the MTB isolates) were found to be large and most of these were multinational and/or mixed, consistent with the high transmission permeability identified in Madrid [15].…”
Section: Discussionsupporting
confidence: 53%
“…Recent studies in Spain have revealed that, in addition to immigrant tuberculosis (TB) cases that appear to have been imported, a proportion of immigrant TB cases are caused by recent transmission after arrival in the host country [9,[13][14][15]. In this situation, the specific analysis of immigrant clusters, especially large clusters, deserves attention.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, reactiva-tion TB was thought to be the cause of active TB in immigrants who originated from areas with high TB prevalences and who are now living in countries with low TB prevalences (26). However, cluster analyses in Spain suggested that recent transmission can be a significant cause of TB infections in immigrants (11,174). While immigration can influence the dynamics of the HIV-TB syndemic, its effect is less marked than that of the smaller-scale internal migration of selected high-risk populations, such as migrant workers in South Africa.…”
Section: Population Mobility Can Shape the Dynamics Of Transmission Omentioning
confidence: 99%
“…The database used in the survey included the genotypes of the M. tuberculosis isolates from 2,669 cases. These were obtained from a multicenter molecular epidemiology study performed over 9 years in Madrid (2001 to 2009) and involving 8 hospitals (19)(20)(21). The sample corresponded to 79% and 32% of all culture-positive cases in immigrants and autochthonous patients, respectively.…”
Section: Discussionmentioning
confidence: 99%